Penerapan Program CSR PLN dalam Pengembangan Literasi melalui Sekolah Sungai Gunung Anyar - Lintang Laxita Chandra Dewi; Buffon Yoppy Trie Ambodo; Muhammad Fadly Miftaqul; Muhammad Roisul Basyar; Wati, Rahmawati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Penerapan Program CSR PLN dalam Pengembangan Literasi melalui Sekolah Sungai Gunung Anyar Literacy is an essential skill that students must master in the era of disruption to face the challenges of the 21st-century digital transformation. One of the key foundational skills is basic literacy, which includes science literacy, numeracy, reading and writing, financial literacy, digital literacy, as well as cultural and citizenship literacy. Education, as a process of character development for the nation, plays a significant role in the development of these skills, particularly in early childhood education that supports physical, cognitive, social, and emotional growth in children. On the other hand, Corporate Social Responsibility (CSR) also plays an important role in enhancing community literacy, as demonstrated by PT PLN (Persero) through the establishment of the Sekolah Sungai in Gunung Anyar Tambak, Surabaya. This CSR program aims to raise environmental literacy awareness, particularly regarding river and mangrove ecosystems, while empowering the local community. This study employs a descriptive qualitative approach to depict the impact of CSR PLN in literacy development through the Sekolah Sungai program, involving a lot of students and local residents. The results indicate that the program successfully raised environmental awareness, strengthened social relationships, and provided economic benefits through waste management and handicrafts. Overall, PT PLN's CSR has a positive impact on community empowerment, improved quality of life, and supports environmental sustainability around the Sekolah Sungai Gunung Anyar Tambak.